Neuronavigated repetitive Transcranial Magnetic Stimulation (rTMS) in Chronic post-Stroke Aphasia Rehabilitation - Georgiou, Anastasios M. (Faculty of Health Sciences, Department of Rehabilitation Sciences, Cyprus University of Technology, 2019)
Aphasia, a disorder of spoken and/or written language, is a significant aftermath of stroke affecting more than a third of all stroke survivors. Many stroke survivors continue to have language deficits greater than six months post-stroke. Numerous studies over the span of more than a decade have shown that transcranial magnetic stimulation (TMS) can facilitate language recovery for patients who suffer from aphasia due to stroke. Transcranial magnetic stimulation creates a fluxing magnetic field, which allows for the generation of weak currents in underlying cortical neurons, causing them to depolarize. Depending on the intensity, frequency and duration of stimulation, TMS can cause decreases or increases in cortical excitability beyond the period of stimulation aiming to facilitate language abilities. The research reported in this thesis is the first of its kind in Cyprus. Specifically, the aim was to investigate the effectiveness of neuronavigated repetitive TMS (rTMS) as a standalone treatment for chronic aphasia post-stroke. A single subject experimental design (SSED) methodology preceded by a pilot study confirming the fidelity of trial procedures and patient acceptability of TMS was adopted. Findings revealed that rTMS over the right pars triangularis (pTr) shows promise to promote neuroplasticity in patients suffering from chronic post-stroke aphasia. Behavioural changes included trends towards improvement in verbal comprehension, expressive language, naming and reading abilities. There was one case that showed significant improvement in spoken comprehension and reading performance. Regarding functional communication, the total number of narrative words increased in three participants and decreased in one participant post-treatment. Quality of life (QoL) did not significantly change as a result of the treatment. Further research exploring individualized TMS protocols for post-stroke aphasia rehabilitation is strongly recommended with the aspiration that TMS will be used as a standard treatment modality in clinical practice in the near future.
Keywords: Stroke; Aphasia; rTMS; cTBS; Systematic review